PROBLEMS ENCOUNTERED BY THE STUDENTS’ IN SPEAKING ENGLISH AT TWELVETH GRADE OF SMAN 2 GEMEH - Reivi Soreh; Noldy Pelenkahu; Meity Muntuuntu (Program Studi Pendidikan Bahasa Inggris, 2022)
This study was aimed to find out the speaking problems encountered by the students’. It was conducted at twelveth grade Of SMAN 2 Gemeh. The design of the research was used descriptive quantitative method. The instrument for data collection was questionnaires distributed to twenty students’ of twelveth grade at SMAN 2 Gemeh. Students' answer to each item in the spread questionnaire were examined and conferred by the researcher's understanding, opinion and experience. The results showed that most of the students’ had problems in speaking, they were linguistic problems and non-linguistic problems. Linguistic problems consisted of poor in grammar, lack of vocabulary and lack of pronunciation. The dominant problem of linguistic problems was poor in grammar. Most of them stated that they were not able to construct English sentences accurately, and for non-linguistic problems were shyness and lack of confidence. It is suggested that the students should study hard and do more practice in speaking.